2017
DOI: 10.1093/neuonc/nox109
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of oral sonidegib (LDE225) in pediatric brain and solid tumors and a phase II study in children and adults with relapsed medulloblastoma

Abstract: Sonidegib was well tolerated and the RP2D in pediatric patients was 680 mg/m2 once daily. Five of the 10 MB patients with activated Hh pathway demonstrated complete or partial responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
136
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(137 citation statements)
references
References 33 publications
1
136
0
Order By: Relevance
“…600 In a phase I study of a 3 + 3 dose escalation to treat small-cell lung cancer patients, sonidegib combined with cisplatin and etoposide sustained PFS in patients with Sox2 amplification. 224 These combinations in a phase II trial for patients with recurrent medulloblastoma resulted in a complete or partial response in 50% of patients 612 and have been used for other cancer treatments in phase I/II clinical trials, such as NCT02111187 for prostate cancer, NCT02027376 for breast cancer, and NCT02195973 for recurrent ovarian cancer.…”
Section: Agents Targeting Csc-associated Signaling Pathways In Clinicmentioning
confidence: 99%
“…600 In a phase I study of a 3 + 3 dose escalation to treat small-cell lung cancer patients, sonidegib combined with cisplatin and etoposide sustained PFS in patients with Sox2 amplification. 224 These combinations in a phase II trial for patients with recurrent medulloblastoma resulted in a complete or partial response in 50% of patients 612 and have been used for other cancer treatments in phase I/II clinical trials, such as NCT02111187 for prostate cancer, NCT02027376 for breast cancer, and NCT02195973 for recurrent ovarian cancer.…”
Section: Agents Targeting Csc-associated Signaling Pathways In Clinicmentioning
confidence: 99%
“…In a trial of adult and pediatric patients with medulloblastoma (and other tumors of the central nervous system [CNS]; NCT01125800; Table 2), a subset of patients without HH-driven tumors (determined by upregulation of GLI1, SHROOM2, sphingosine kinase-1, and PDLIM3, and the downregulation of orthodenticle homeobox 2) failed to respond to sonidegib. In total, 50% (5/10) of patients with HH-driven tumors had complete or partial responses to sonidegib; however, the prepubertal patients showed signs of premature growth plate closure [57]. In another trial of 31 patients with recurrent medulloblastoma, vismodegib was found to have activity only if the medulloblastoma was HH-driven (NCT00939484; Table 2) [58].…”
Section: Medulloblastomamentioning
confidence: 99%
“…SHH pathway inhibitors are attractive options for adult SHH medulloblastoma, as the toxicity of these compounds on growth plates is not a concern, and adult SHH medulloblastomas frequently harbor mutations upstream . Vismodegib and sonidegib have shown considerable efficacy in the relapsed setting and may be an option for upfront combination therapy . Future clinical trials need to address both the issue of addition of SMO inhibitors as well as the role and toxicity of adjuvant chemotherapy in this population.…”
Section: Epidemiologymentioning
confidence: 99%
“…96 Vismodegib and sonidegib have shown considerable efficacy in the relapsed setting and may be an option for upfront combination therapy. 97,98 Future clinical trials need to address both the issue of addition of SMO inhibitors as well as the role and toxicity of adjuvant chemotherapy in this population. Moreover, longer follow-up is mandatory for adult medulloblastoma studies due to the high frequency of late relapses.…”
Section: Medulloblastomamentioning
confidence: 99%